1997
DOI: 10.1080/10473289.1997.10464454
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Hexavalent Chromium in Southwestern Ontario

Abstract: This study reports the first field measurements of airborne hexavalent chromium (Cr(vi)) in southwestern Ontario. Hexavalent chromium was identified as an inhalation carcinogen and an air toxic of concern during the 1991-93 Windsor Air Quality Study. The results of that study indicated that approximately 20% of the routinely monitored ambient airborne chromium (Cr) was in the hexavalent form. In addition, the range of carcinogenic health risks attributable to airborne Cr(vi) was determined to be between 1.4 × … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…Species without any unit risk values were not included in the risk assessment process. The unit risk of chromium was adjusted by multiplying a factor of 0.2, assuming that approximately 20% of the ambient airborne chromium was in the toxic hexavalent form (Bell and Hipfner, 1997). The unit risk for nickel was adopted from the unit risk for nickel subsulfide in IRIS, assuming that all the monitored nickel was in the insoluble and carcinogenic form.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…Species without any unit risk values were not included in the risk assessment process. The unit risk of chromium was adjusted by multiplying a factor of 0.2, assuming that approximately 20% of the ambient airborne chromium was in the toxic hexavalent form (Bell and Hipfner, 1997). The unit risk for nickel was adopted from the unit risk for nickel subsulfide in IRIS, assuming that all the monitored nickel was in the insoluble and carcinogenic form.…”
Section: Risk Assessmentmentioning
confidence: 99%
“…According to Bell and Hipfner (1997), the mean Cr(VI) level in industrial areas in Hamilton, where a number of steel manufacturing companies are located, was 0.55 ng/m 3 . Li et al (2002) reported that the Cr(VI) levels in Sydney, Australia were 0.14 in a residential area and 0.2-1.3 ng/m 3 in an industrial area.…”
Section: Comparison Of Cr(vi) Levels In Koreamentioning
confidence: 99%
“…2 ), whereas Cr(III) exists as cations (Cr 31 , Cr(OH) 21 , Cr(OH) 2 1 ). 42 Protonation/deprotonation of Cr(III) is kinetically rapid, 41 further emphasizing the importance of solution acidity or basicity.…”
Section: Influence Of Phmentioning
confidence: 99%
“…19,20 Almost all Cr(VI) present in the environment comes from anthropogenic sources, as this species is ordinarily converted to Cr(III) via natural and often rapid chemical reduction. [21][22][23] In occupational settings, airborne Cr(VI) compounds can be found in a wide range of concentrations and particle sizes, and also in the presence of Cr(III) compounds with widely varying ratios. 24 The toxicity of airborne Cr(VI) compounds is quite varied and depends in part on the solubility of the Cr(VI) compound in question.…”
Section: Introductionmentioning
confidence: 99%